Autonomous Maintenance Program For Job Base In Technical University - Wan Mahmood, Wan Hasrulnizzam; Mahmood, Ab Rahman; Abdullah, Ilyana (2008)

(untitled)
This paper discusses the implementation of Autonomous Maintenance (AM) program for job base in order to sustain the machine efficiency in Technical University (TU). Grinding machine was selected for case study. In TU, all engineering students especially will use grinding machine for producing very fine finishes or making very light cuts, using an abrasive wheel as the cutting device. As compared with other machining processes, grinding is a costly operation that should be utilised under optimal conditions. The result shows that the AM program had improved responsibility and alertness of the machine users on the machine condition as the standard. In addition, it reduced the total of the problems occurred on the machine and indirectly reduced the cost of breakdown maintenance.